Measurements of pressure broadening coefficients of selected transitions in the 2 nu(5) band of formaldehyde - Barry, H; Corner, L; Hancock, G; Peverall, R; Ranson, T; Ritchie, G (2003)
A tunable diode laser and a low finesse optical cavity are used to probe formaldehyde on four selected rotational transitions within its 2υ5 overtone band around 1.76 μm by cavity enhanced absorption spectroscopy (CEAS). Pressure broadening coefficients for these transitions in the presence of a variety of gases (He, Ne, Ar, Kr, N2, O2 and H 2O, and also for CH2O itself) have been determined. The variation in the pressure broadening cross sections with molecular parameters of the colliding partners is discussed in terms of multipole interactions and compared with previous results and with inelastic collision probabilities. For the rare gases the pressure broadening parameters are shown to be strongly correlated with the intermolecular well depth between CH2O and each collider.